2010
DOI: 10.1007/s00468-010-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of climatic variability on δ13C and tree-ring growth in piñon pine (Pinus edulis)

Abstract: Understanding the response of long-lived species to natural climatic variability at multiple scales is a prerequisite for forecasting ecosystem responses to global climate change. This study investigated the response of piñon pine (Pinus edulis) to natural climatic variability using information on physiology and growth as recorded in leaves and tree rings. d 13 C of annual leaf cohorts (d 13 C leaf ) and tree rings (d 13 C ring ) were measured at an ecotonal/xeric site and a mid-range/mesic site. Ring width in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In piñon pine, high spring and summer temperatures during the year of cone maturation acted to decrease cone development (Appendix : Table S5); high growing season temperatures are known to reduce vegetative growth in piñon pine (Newberry ), and Williams and Ehleringer () found that piñon pine root activity is sensitive to higher soil temperatures, resulting in decreased uptake of summer precipitation in shallow surface soil layers.…”
Section: Discussionmentioning
confidence: 99%
“…In piñon pine, high spring and summer temperatures during the year of cone maturation acted to decrease cone development (Appendix : Table S5); high growing season temperatures are known to reduce vegetative growth in piñon pine (Newberry ), and Williams and Ehleringer () found that piñon pine root activity is sensitive to higher soil temperatures, resulting in decreased uptake of summer precipitation in shallow surface soil layers.…”
Section: Discussionmentioning
confidence: 99%
“…Because annual variations in photosynthetic conditions are reflected in the carbon isotope composition of tree rings (Wilson and Grinsted 1977), the use of stable carbon isotope analysis (d 13 C) of tree rings to evaluate plantenvironment interactions and plant responses to environmental change has been rapidly expanding (Joshua and Evans 1999;Liu et al 2004;Tardif et al 2008). Interannual tree-ring d 13 C variations have been found to correlate with tree species and a wide range of environmental variables such as carbon dioxide concentration in the air, light availability (Francey and Farquhar 1982;Berry et al 1997), soil water conditions (Sheu et al 1996), humidity (Hemming et al 1998;Crockett et al 2010), cloud cover (Ramesh et al 1986), temperature (Anderson et al 1998), precipitation (Fichtler et al 2010), drought and moisture stress (Leavitt 1989;Newberry 2010) and other environmental factors (Adams and Grierson 2001;McCarroll et al 2009;Savard 2010). Advances in measurement techniques for carbon isotope analysis, such as the new on-line (continuous flow) method and pooled sample methods ) have resulted in a vast quantity of reliable data regarding stable carbon isotopes and their responses to environmental factors.…”
Section: Introductionmentioning
confidence: 98%
“…Their results show that the responses are region-dependent, suggesting that trees use different adaptation strategies in response to environmental change. Increasing iWUE levels do not always enhance tree radial growth rates due to the interaction with different growth conditions and tree species (Newberry, 2010;Andreu-hayles et al, 2011;Gyenge et al, 2012;Brito et al, 2016). In China, studies have been performed in water-limited area (Wang et al, 2012;Xu et al, 2013;Wu et al, 2015), and their results show that the tree radial growth rates do not accelerate when iWUE increases significantly.…”
Section: Introductionmentioning
confidence: 99%